Genome-Scale Screening and Combinatorial Optimization of Gene Overexpression Targets to Improve Cadmium Tolerance in Saccharomyces cerevisiae - Chen, Yongcan; Liang, Jun; Chen, Zhicong; Wang, Bo; Si, Tong (Frontiers in Microbiology, 2021)
Heavy metal contamination is an environmental issue on a global scale. Particularly, cadmium poses substantial threats to crop and human health. Saccharomyces cerevisiae is one of the model organisms to study cadmium toxicity and was recently engineered as a cadmium hyperaccumulator. Therefore, it is desirable to overcome the cadmium sensitivity of S. cerevisiae via genetic engineering for bioremediation applications. Here we performed genome-scale overexpression screening for gene targets conferring cadmium resistance in CEN.PK2-1c, an industrial S. cerevisiae strain. Seven targets were identified, including CAD1 and CUP1 that are known to improve cadmium tolerance, as well as CRS5, NRG1, PPH21, BMH1, and QCR6 that are less studied. In the wild-type strain, cadmium exposure activated gene transcription of CAD1, CRS5, CUP1, and NRG1 and repressed PPH21, as revealed by real-time quantitative PCR analyses. Furthermore, yeast strains that contained two overexpression mutations out of the seven gene targets were constructed. Synergistic improvement in cadmium tolerance was observed with episomal co-expression of CRS5 and CUP1. In the presence of 200 μM cadmium, the most resistant strain overexpressing both CAD1 and NRG1 exhibited a 3.6-fold improvement in biomass accumulation relative to wild type. This work provided a new approach to discover and optimize genetic engineering targets for increasing cadmium resistance in yeast.